Transactions Of Agricultural Land Revenue By Act No. 2 Of 1960 On Sharing Agreement In District Anjatan Of Indramayu - Mentari Dessy Wijayanti; Akhmad Khisni (Jurnal Akta, 2019)
The purpose of this study was to know and understand execution of transactions for the results of agricultural land pursuant to Act No. 2 of 1960 on Revenue Sharing Agreement in the district Anjatan of Indramayu and to know, understand, and analyze constraints and solutions in transactions for the results of agricultural land pursuant to Act No. 2 of 1960 on Revenue Sharing Agreement in the district Anjatan of Indramayu.Based on the analysis concluded that the implementation of the agreement for the results of agricultural land in the district Anjatan of Indramayu  has not entirely based on the provisions of Act No. 2 of 1960 on revenue-sharing agreements, since in fact the local community in terms of the implementation of revenue-sharing agreements mainly staple crops still based on the provisions of customary law and local practice, it can be seen from the shape of the agreement, the term of the agreement and the division of land results in the implementation of agricultural land revenue sharing agreements. Factors that hinder the implementation of revenue-sharing agreements on agricultural land in the district Anjatan of Indramayu  according to Act No. 2 of 1960 on revenue sharing agreements often expressed by farmers when the implementation of revenue-sharing agreements follow the rules of the Act is the problem of a complicated process and timeframes long for the manufacture of revenue-sharing agreements.Keywords: Transaction; Agreement; Sharing.